Discourse Criticism in Social Media: A Critical Discourse Analysis of Youth Identity Representation on Instagram - Rosalina, Afni; Suhadi, Jumino; Pratiwy, Devi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine how youth identities are represented within social media discourse, particularly on the Instagram platform. Employing Critical Discourse Analysis (CDA) based on Norman Fairclough’s framework, this research explores the relationship between language, power, and ideology in the production and consumption of digital content. The data were collected from Instagram posts and captions that depict Indonesian youths’ lifestyle, self-expression, and social image. The findings reveal that youth identity representations on Instagram are often constructed through consumptive symbols, visual aesthetics, and narratives of freedom and authenticity. However, beneath these narratives lie the hegemonic influence of popular culture and social pressure to perform an idealized self-image. The study concludes that social media functions not merely as a space for self-expression but as an arena of discursive struggle where meanings and power relations shape youth identities. This research contributes to critical discussions on how digital media mediates the construction of identity in contemporary society.